EKONOMI KREATIF DALAM PEMANFAATAN BUAH HANJELIN SEBAGAI SOUVENIR LOKAL DI BAHO FARM - Anugerah Gita Pratami Harefa; Demetrius Wau; Fedius Ndruru; Fransiskus Gaurifa; Imelda Putri Halawa; Kristina Giawa; Kurbanus Finowaa; Linglen Bertha Dachi; Merri Anna Kristin Laia; Yurli Bohalima (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
This study examines the potential of the creative economy in utilizing Hanjelin fruit (Coix lachryma-jobi L.) as a local souvenir at Baho Farm, Nias. Baho Farm, as a nature-based tourism and outbound destination, has significant opportunities to develop derivative products from local resources in order to enhance economic value and tourist attraction. Hanjelin fruit, which grows abundantly in Nias, possesses unique characteristics but has not yet been optimally utilized as a creative economic product. The objectives of this study are to identify the potential of Hanjelin as a raw material for souvenir products, analyze relevant production and marketing processes, and evaluate the impact of developing Hanjelin-based souvenirs on the local economy and the sustainability of tourism at Baho Farm. The research employs a qualitative approach using a case study method, involving in-depth interviews with Baho Farm managers, local artisans, and visitors, as well as participatory observation. The findings of this study are expected to provide strategic recommendations for Baho Farm and related stakeholders in developing Hanjelin into competitive, innovative, and sustainable souvenir products, while simultaneously strengthening the local cultural identity of Nias through the creative economy.